Li2S6‐Integrated PEO‐Based Polymer Electrolytes for All‐Solid‐State Lithium‐Metal Batteries. (30th June 2021) - Fang, Ruyi; Xu, Biyi; Grundish, Nicholas S.; Xia, Yang; Li, Yutao; Lu, Chengwei; Liu, Yijie; Wu, Nan; Goodenough, John B.
Abstract: The integration of Li2 S6 within a poly(ethylene oxide) (PEO)‐based polymer electrolyte is demonstrated to improve the polymer electrolyte's ionic conductivity because the strong interplay between O 2− (PEO) and Li + from Li2 S6 reduces the crystalline volume within the PEO. The Li/electrolyte interface is stabilized by the in situ formation of an ultra‐thin Li2 S/Li2 S2 layer via the reaction between Li2 S6 and lithium metal, which increases the ionic transport at the interface and suppresses lithium dendrite growth. A symmetric Li/Li cell with the Li2 S6 ‐integrated composite electrolyte has excellent cyclability and a high critical current density of 0.9 mA cm −2 at 40 °C. Impressive electrochemical performance is demonstrated with all‐solid‐state Li/LiFePO4 and high‐voltage Li/LiNi0.8 Mn0.1 Co0.1 O2 cells at 40 °C. Abstract : Li2 S6 is used as an additive for a PEO‐LiTFSI polymer electrolyte and serves to improve the Li + ‐ion conductivity of the electrolyte by reducing the crystalline volume in the PEO as well as aiding in the formation of a thin stable layer that stabilizes the interface with lithium metal. This leads to an impressive electrochemical performance at 40 °C in all‐solid‐state full cells with a lithium metal anode and an LiFePO4 or LiNi0.8 Mn0.1 Co0.1 O2 cathode.